2019
DOI: 10.1002/jimd.12028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of enzyme replacement therapy with galsulfase in mucopolysaccharidosis type VI treatment: Systematic review

Abstract: Introduction: Mucopolysaccharidosis VI is a rare disease characterized by the arylsulfatase B enzyme deficiency, which is responsible for different clinical manifestations. The treatment consists of enzyme replacement therapy with intravenous administration of galsulfase. Objective: Evaluate the effectiveness of the enzyme replacement therapy with galsulfase for the mucopolysaccharidosis VI treatment. Method: Systematic review of observational studies. The databases of PubMed, Cochrane Library, Lilacs, and Jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…They did not select other study designs Brunelli et al (2016) They selected one randomized study. They did not combine results from different study designs Gomes et al (2019) The effectiveness of ERT was identified by a qualitative assessment of each study report. The outcomes were classified as primary and substitutive according to the authors' assessment MPS, muchopolysaccharidosis; ERT, enzyme replacement therapy; GRADE, grading of recommendations assessment, development and evaluation; HSCT, hematopoietic stem cell transplant; 6-MWT, 6-min walk test.…”
Section: Discussionmentioning
confidence: 99%
“…They did not select other study designs Brunelli et al (2016) They selected one randomized study. They did not combine results from different study designs Gomes et al (2019) The effectiveness of ERT was identified by a qualitative assessment of each study report. The outcomes were classified as primary and substitutive according to the authors' assessment MPS, muchopolysaccharidosis; ERT, enzyme replacement therapy; GRADE, grading of recommendations assessment, development and evaluation; HSCT, hematopoietic stem cell transplant; 6-MWT, 6-min walk test.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options vary depending on the MPS subtype. ERT is the most common treatment for MPS, with approved therapies available for [51,52], MPS II [30], MPS IVA [85][86][87], MPS VI [37], and MPS VII [103,104]. Research on the effects of ERT on audiological function has been inconclusive [53].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the effects of ERT on audiological function has been inconclusive [53]. While case reports on MPS IVA [88] and MPS VI [38,39] have described hearing improvement after ERT, studies on MPS I [21] and MPS VI [37] have described no change in audiological function after ERT. A MPS II murine model found that ERT was able to improve the conductive component, but was unable to ameliorate the sensorineural component [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations